Trimester-specific thyroid hormone reference ranges in Sudanese women. Issue 1 (December 2016) - Elhaj, Enaam; Adam, Ishag; Ahmed, Mohamed; Lutfi, Mohamed
Abstract Background Trimester-specific reference ranges for T3, T4, and TSH need to be established in different communities. Neither Sudan nor other African countries have established trimester-specific reference ranges for TSH, free T3 (FT3), and free T4 (FT4) in healthy pregnant women. This study aimed to establish trimester-specific reference ranges for TSH, FT3, and FT4 in healthy pregnant Sudanese women. Results We performed a longitudinal study, which included 63 women with singleton pregnancies who were followed since early pregnancy until the third trimester. The study was performed in Saad Abu-Alela Hospital, Khartoum, Sudan, during January to October 2014. An equal number of age- and parity-matched non-pregnant women were enrolled as a control group. Basic clinical and obstetrics data were gathered using questionnaires. TSH, FT3, and FT4 levels were measured. Median (5th–95th centile) values of TSH, FT3, and FT4 were 1.164 IU/ml (0.079–2.177 IU/ml), 4.639 nmol/l (3.843–6.562 nmol/l), and 16.86 pmol/l (13.02–31.48 pmol/l) in the first trimester. Median values of TSH, FT3, and FT4 were 1.364 IU/ml (0.540–2.521 IU/ml), 4.347 nmol/l (3.425–5.447 nmol/l), and 13.51 pmol/l (11.04–31.07 pmol/l) in the second trimester. These values were 1.445 IU/ml (0.588–2.460 IU/ml), 4.132 nmol/l (3.176–5.164 nmol/l), and 12.87 pmol/l (9.807–23.78 pmol/l) in the third trimester, respectively. TSH levels increased throughout the trimesters. FT3 and FT4 levels were significantly higher in the first trimester compared with the second and third trimesters. TSH, FT3, and FT4 levels were significantly lower in pregnant women compared with non-pregnant women (P < 0.001). Conclusions The present study is the first to establish trimester-specific reference ranges of TSH, FT3, and FT4 in Sudanese women with normal pregnancies. Our results suggest that pregnancy is likely to suppress TSH, T3, and T4 levels in healthy women.